Treatment of Bacillus cereus endophthalmitis with endoscopy-assisted vitrectomy - Pan, Qintuo (Medicine (Baltimore), 2017)
To evaluate the use of endoscopy-assisted vitrectomy in patients with sight-threatening Bacillus cereus endophthalmitis. A retrospective analysis was conducted in 15 eyes with Bacillus cereus endophthalmitis. Patients were divided into 2 groups: endoscopy-assisted vitrectomy (5 eyes) and conventional vitrectomy (10 eyes). The following clinical data were recorded and analyzed: sex, age, latent period, symptom duration, follow-up time, visual acuity pre- and postsurgery, recurrence of endophthalmitis, incidence of phithisis bulbi, and incidence of enucleation. In the conventional vitrectomy group, postoperative visual acuity ranged from no light perception in 5 patients (50%), light perception in 3 patients (30%), 20/1000 in 1 patient (10%), and 20/50 in 1 patient (10%). In the endoscopy-assisted vitrectomy group, postoperative visual acuity ranged from no light perception in 2 patients (40%), light perception in 1 patient (20%), and hand movements in 2 patients (40%). There was no statistically significant difference between the 2 groups in terms of the final postoperative visual acuity (F = 0.006, P = .937). There is no difference between the 2 groups in terms of the incidence of enucleation. The median symptom duration was 4 hours (range: 2–6 hours) in the conventional group and 9 hours (range: 7–11 hours) in the endoscopy-assisted vitrectomy group. The difference in the symptom duration between the 2 groups was statistically significant (P = .002). There is no statistical significant difference between the 2 groups in terms of visual acuity and incidence of enucleation. Therefore, endoscopy-assisted vitrectomy can be considered as an alternative treatment for treatment of B cereus endophthalmitis particularly for cases when symptom duration was more than 6 hours.